Nanophotonics-based low-temperature PECVD epitaxial crystalline silicon solar cells. (14th March 2016) - Chen, Wanghua; Cariou, Romain; Foldyna, Martin; Depauw, Valerie; Trompoukis, Christos; Drouard, Emmanuel; Lalouat, Loic; Harouri, Abdelmounaim; Liu, Jia; Fave, Alain; Orobtchouk, Régis; Mandorlo, Fabien; et al.
Abstract: The enhancement of light absorption via nanopatterning in crystalline silicon solar cells is becoming extremely important with the decrease of wafer thickness for the further reduction of solar cell fabrication cost. In order to study the influence of nanopatterning on crystalline silicon thin-film solar cells, we applied two lithography techniques (laser interference lithography and nanoimprint lithography) combined with two etching techniques (dry and wet) to epitaxial crystalline silicon thin films deposited via plasma-enhanced chemical vapor deposition at 175 °C. The influence of nanopatterning with different etching profiles on solar cell performance is studied. We found that the etching profiles (pitch, depth and diameter) have a stronger impact on the passivation quality (open circuit voltage and fill factor) than on the optical performance (short circuit current density) of the solar cells. We also show that nanopatterns obtained via wet-etching can improve solar cell performance; and in contrast, dry-etching leads to poor passivation related to the etching profile, surface damage, and/or contamination introduced during the etching process.